PERAN KOORDINASI PEMERINTAH PROVINSI SUMATERA BARAT DALAM PENANGGULANGAN RADIKALISME DAN TERORISME - Wani Fitriyanti; Adil Mubarak (LPPM Universitas Abdurrab, 2024)
This research aims to analyze the coordination role of the West Sumatra government in countering radicalism and terrorism, identify factors that influence coordination, and solutions to overcome them. Although the West Sumatran provincial government's efforts are significant, the index of potential radicalism (IPR) is still high, indicating the need for more effective coordination between government agencies. This quasi-qualitative research uses literature and field studies through interviews, documentation and non-participant observation. The results show that inter-agency coordination is influenced by the factors of unity of action, division of labor, communication, and discipline, and is still constrained by internal and external factors such as the absence of a clear legal umbrella, lack of distribution of data access, and the influence of social media. The conclusion of this study emphasizes the need to strengthen regulations and coordination guidelines, distribute data access, and optimize activity scheduling. The implications of the findings provide recommendations for the provincial government in developing policies and guidelines for more effective coordination.